1966
DOI: 10.1080/00049158.1966.10675415
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Nutrient Uptake by Flooded Gum Seedlings Subjected to Various Phosphorus Supplies

Abstract: In a study of the mineral nutrition of flooded gum E. grandis Hill ex Maiden in a controlled environment, it was noted that anthocyanin colouration of the upper leaf surface resulted from phosphorus deficiency. Increase in phosphorus supply with other nutrient elements supplied at constant levels resulted in (I) an increase in seedling dry-weight and stem-leaf ratio, and a decrease in root-shoot ratio, and (2) a general increase in tissue concentration of nitrogen, phosphorus and potassium, a general decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

1977
1977
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 13 publications
1
1
0
1
Order By: Relevance
“…This indicates clearly that the seedlings were able to acquire P in order to support growth. For comparison, total seedling P content in our study was similar to that found after about 2 months growth of E. grandis seedlings (Lacey et al, 1966) and 3 months growth of E. pilularis seedlings under conditions of low P supply with P added in inorganic nutrient solution (Mulligan and Sands, 1988). However, it is uncertain to what extent E. globulus seedlings would take up P from light fraction organic matter when grown without P limitation.…”
Section: Seedling Growthsupporting
confidence: 78%
“…This indicates clearly that the seedlings were able to acquire P in order to support growth. For comparison, total seedling P content in our study was similar to that found after about 2 months growth of E. grandis seedlings (Lacey et al, 1966) and 3 months growth of E. pilularis seedlings under conditions of low P supply with P added in inorganic nutrient solution (Mulligan and Sands, 1988). However, it is uncertain to what extent E. globulus seedlings would take up P from light fraction organic matter when grown without P limitation.…”
Section: Seedling Growthsupporting
confidence: 78%
“…These data therefore indicate a relationship between growth and foliar nutrients concentrations. A positive correlation between foliar nutrient concentrations and growth has been demonstrated for several Eucalyptus grown in solution culture (Kaul et al, 1970;Lacey et al, 1966). Whilst such relationships are more difficult to establish in field situations, examination of young seedling in pots have shown that they do exist.…”
Section: Discussionmentioning
confidence: 98%
“…En el suelo arcilloso la fertilización estimuló la producción de hojas y el crecimiento de las plantas por ser el P limitante en este tipo de suelo. El área foliar de la planta modula la tasa de crecimiento (Lambers et al 1998) En plantines de Eucalyptus grandis en hidroponia suplementados con P, se observó que al aumentar la dosis aplicada, se incrementaba la materia seca acumulada en tallo y hojas, al igual que las relaciones tallo:total y hojas:total, aunque el tallo se incrementaba más que las hojas (Lacey et al 1966). Sin embargo, en ensayos en aeroponia con esta misma especie, se observó que la proporción de tallo no se modificaba al aumentar la dosis de P aplicada, mientras que la proporción de hojas aumentaba y la de raíces disminuía (Kirschbaum et al 1992).…”
Section: Resultsunclassified